New CSMA/CA prioritisation based on fuzzy control mechanism. (2017) - Bouazzi, Imen; Bhar, Jamila; Atri, Mohamed
Wireless sensor networks (WSNs) consist of several small nodes that use different types of sensors to gather different types of data and to communicate with each other through several protocols. The IEEE 802.15.4 presents a soft medium access control (MAC) protocol that provides good efficiency for data transmission by adapting its parameters according to characteristics of different applications. The main idea of this paper is to apply a dynamic allocation of priority level for nodes that compete for the access to the medium through tuning parameters in the carrier sense multiple access/collision avoidance (CSMA/CA) algorithm. A priority scheduling is achieved using a fuzzy logic mechanism exploiting queue level and traffic rate of each node in order to ensure adequate dynamic allocation. This paper demonstrates various advantages of priority-based CSMA/CA for quality of service (QoS). Results show significant improvements achieved by our approach among the IEEE 802.15.4 MAC standards.